Virtual Reality as Distraction Analgesia for Office-Based Procedures: A Randomized Crossover-Controlled Trial. (March 2021) - Gray, Mingyang L.; Goldrich, David Y.; McKee, Sean; Schaberg, Madeleine; Del Signore, Anthony; Govindaraj, Satish; Iloreta, Alfred Marc
Objective: The purpose of this study was to explore the use of immersive and interactive virtual reality (VR) for analgesia, anxiety reduction, and overall satisfaction in patients undergoing outpatient postoperative debridements. Study Design: Randomized crossover-controlled trial. Setting: Academic outpatient clinic. Subjects and Methods: Adult patients who had functional endoscopic sinus surgery and skull base surgery and were undergoing office-based postoperative nasal endoscopy and debridement were recruited and followed for 2 consecutive office visits. Participants were randomized to receive either the control or experimental analgesia for the first postoperative visit (PO1) and crossed over into the opposite treatment arm during the second postoperative visit (PO2). Outcomes included procedural pain, anxiety and satisfaction scores, procedural time, and reflexive head movements per minute (RHM). Results: Eighty-two participants were recruited. At PO1, 39 received standard analgesia, and 43 received an immersive VR experience. At PO1, the VR group experienced significantly less anxiety ( P = .043) and fewer RHM ( P = .00016) than the control group. At PO2, the VR group experienced significantly fewer RHM ( P = .0002). At PO2, patients who received the experimental treatment after initially receiving the control treatment had significantly decreased pain, anxiety, and RHM. This effect was not seen in the second group. Overall, 69.51% of patients felt that the VR treatment was better; 19.51% thought that it was the same; and 9.76% found it to be worse. Conclusion: VR technology holds promise as a nonpharmacologic analgesic and anxiolytic intervention for otolaryngology office-based procedures. Further study of VR use in other procedures is warranted. Level of Evidence: 1, randomized controlled trial.